EVALUATION THROUGH ANALYSIS OF VISUAL MATERIALS IN THE SOCIAL STUDIES EDUCATION - Mustafa İÇEN (Fırat University, 2020)
It is revealed by various studies that most of what we have learned in the educational environment is done with pictures and similar visuals among various materials addressing the sense of sight. In visual communication, it is important to be able to read the meaning and thoughts of visual symbols. Understanding, reading, interpreting and using visual symbols within the concept of visual literacy is important for an individual to communicate effectively. Most of the students' knowledge is experienced in a visual world where they learn from media communication tools. Therefore, the use of visual materials in teaching Social Studies course is of great importance. In this context, the problem of the research is to determine the effectiveness of teaching and evaluation through the analysis of visual materials. This is a qualitative research. Document analysis, one of the qualitative research models, was used as a research method and suggestions were made.